The regulatory mechanism of garlic skin improving the growth performance of fattening sheep through metabolism and immunity - Xu, Yongjie; Yi, Mingliang; Sun, Shixin; Wang, Lei; Zhang, Zijun; Ling, Yinghui; Cao, Hongguo (Frontiers in Veterinary Science, 2024)
Objective:Garlic skin (GAS) has been proven to improve the growth performance of fattening sheep. However, the mechanism by which GAS affects fattening sheep is not yet clear. The aim of this study is to investigate the effects of adding GAS to feed on the growth performance, rumen and fecal microbiota, serum and urine metabolism, and transcriptomics of rumen epithelial cells in fattening sheep. Methods: GAS with 80 g/kg dry matter (DM) was added to the diet of fattening sheep to study the effects of GAS on gut microbiota, serum and urine metabolism, and transcriptome of rumen epithelial tissue in fattening sheep. Twelve Hu sheep (body weights; BW, 23.0 ± 2.3 kg and ages 120 ± 3.5 d) were randomly divided into two groups.The CON group was the basal diet, while the GAS group was supplemented with GAS in the basal diet. The trial period was 10 weeks, with the first 2 weeks being the pre-trial period. Results: The daily average weight gain of fattening sheep in the GAS group was significantly higher than that in the CON group (p<0.05), and the serum GSH-Px of the GAS group fattening sheep was significantly increased, while MDA was significantly reduced (p<0.05). Based on the genus classification level, the addition of garlic peel in the diet changed the intestinal microbial composition, and the relative abundance was significantly upregulated by Metanobrevibater (p<0.05), while significantly downregulated by Akkermansia, Parasutterella, and Guggenheimella (p<0.05).Metabolomics analysis found that there were 166 significantly different metabolites in serum and 68 significantly different metabolites in urine between the GAS and CON groups (p<0.05). GAS had an impact on amino acid metabolism, pyrimidine metabolism, methane metabolism, riboflavin metabolism, and unsaturated fatty acid synthesis pathways (p<0.05). Transcriptome sequencing showed that differentially expressed genes were mainly enriched in immune regulatory function, improving the health of fattening sheep. Conclusion: Adding GAS can improve the energy metabolism and immune function of fattening sheep by altering gut microbiota, metabolome, and transcriptome, thereby improving the growth performance of fattening sheep.